THE EFFECT OF TOTAL PHSYICAL RESPONSE (TPR) METHOD ON STUDENTSâ€™ SPEAKING ACHIEVEMENT; A CASE OF NINETH GRADE STUDENTS OF SMPN 1 KABAWO - Siti Wardani, Waode; Nurnia, Nurnia; Siam, Siam (Journal of Teaching English, 2019)
This study was aimed at finding out whether there is a significanteffect of Total Physical Response (TPR) method on studentsâ€™speaking achievement. The research question addressed was â€œisthere any significant effect of Total Physical Response (TPR) methodon studentsâ€™ speaking achievement?â€ The design of study was quasiexperimental design by using two classes, namely experimentalclass and control class. This study involved the ninth gradestudents of SMPN 1 Kabawo who were registered in the academicyear 2017/2018. The instrument of the study was oral test wherethe students performed in front of the class orally about how tomake a glass of ice lemon in 3 minutes. The study usedindependent sample t- test to analyze the data. The result showedthat the studentsâ€™ speaking score in experimental class (3.12) washigher than studentsâ€™ speaking score in control class (2.23). Theresult of hypothesis testing revealed that the level of significant was0.00. It means that there was a significant difference on studentsâ€™speaking achievement after being taught by using total physicalresponse.Keywords: Speaking, Teaching Speaking, Total Physical Response